Challenges and innovative solutions of space-ground integrated network security - LI Jinhui; HUANG Chengbin; WANG Jinhua; LIU Yang (Dianxin kexue)
The security challenges confronting the space-ground integrated network in 6G era were mainly disscussed, and an innovative scheme based on quantum security was proposed. Firstly, the developmental backdrop and evolving trends of the integrated network’s architecture were outlined, highlighting the distinct features and application contexts of both the transparent forwarding and on-board regeneration frameworks. Secondly, the security challenges faced by the space-ground integrated network were analyzed, especially the risks of data transmission security and access authentication. In response to these challenges, the innovative solutions were proposed to ensure the security of the space-ground integrated network based on quantum technology. By leveraging the unconditional security of quantum communication and the advantages of post-quantum cryptographic algorithms, end-to-end secure communication protection for the space-ground integrated network was provided. Finally, the feasibility of using quantum technology was verified to ensure the security of the space-ground integrated network.